P = 2b + 2h
P-2h=2b
b= (P-2h)/2
2007-01-25 06:25:12
·
answer #1
·
answered by 7
·
0⤊
0⤋
P = 2b + 2h
=> 2b = P-2h
=> b = (P - 2h) / 2
or b = (P/2) - h
2007-01-25 06:25:38
·
answer #2
·
answered by Manisha 4
·
0⤊
0⤋
P = 2b + 2h
P-2h=2b
*** the answer is:
b= (P-2h)/2
2007-01-25 06:30:47
·
answer #3
·
answered by sakura ♥ 3
·
0⤊
0⤋
Stop posting your homework questions and try to do them yourself. The several answers to your now 5 questions should be more than enough to help you out.
2007-01-25 06:48:51
·
answer #4
·
answered by lil e 2
·
0⤊
0⤋
once you're asked to unravel for a variable, meaning to get it on one component by ability of itself. a). P = a + b + c >>>>>considering the fact that a and b are beneficial, subtract a and b from the two factors P - a - b = c b). A = a million/2 bh >>>>>considering the fact that a million/2 and b are interior the equation with multiplication, then divide the two factors A/ (a million/2 b) = h = 2A/b C). C = 2 ? r >>>>>> returned, divide to pass to the different component C / 2 ? = r D). rt = d >>>>>Divide the two factors by ability of t r = d/t
2016-11-01 06:46:33
·
answer #5
·
answered by ? 4
·
0⤊
0⤋
Boy you're in trouble when you get this on the exam.
2007-01-25 06:26:33
·
answer #6
·
answered by Gene 7
·
0⤊
0⤋
P- 2h = 2b
P - 2h
--------- = b
2
2007-01-25 06:27:54
·
answer #7
·
answered by Michael L 1
·
0⤊
0⤋